Influence of drug shortages on the well-being at work of pharmacists practicing in community pharmacies - Beuriot Juliette; Crunenberg Robin (Elsevier, 2024)
Introduction: The problem of drug shortages is not new, but it has reached unprecedented levels in recent years. In community pharmacies, pharmacists are forced to develop daily strategies to deal with such shortages and ensure patient care. These efforts result in significant constraints and adjustments to pharmacists' daily practices. The aim of this study is to explore the possible relationship between the consequences of drug shortages and the well-being of pharmacists in pharmacies. Material & method: This study adopts an exploratory qualitative approach by interviewing pharmacists working in community pharmacies in Wallonia. The data were collected between March and June 2023 through individual semi-structured interviews using a resolute guide. The interview guide was adapted as the interviews progressed and according to the pharmacists' views. 16 participants were included, including 7 owner pharmacists, 3 non-owners, and 6 non-titular pharmacists. The interviews were transcribed and then analyzed through a thematic approach. Results: An in-depth study of the day-to-day reality of pharmacies that is open to the public highlights the time-consuming nature of drug shortages, with various implications for pharmacists' relationships, finances, and workload. However, these professionals also highlight the recognition of patients when a solution is discovered, with some sources saying that shortages value the pharmacist's ability and enhance the profession. Finally, about the possibility of change in the training of pharmacists is also addressed by some pharmacists. Conclusion: Drug shortages demand changes in pharmaceutical practice and appear to affect the well-being of pharmacists in public settings. However, the impact seems complex and is amplified by the lack of personnel. With shortages continuing to rise in recent years, it would be wise to analyze the longer-term effects of this phenomenon.